Analysis of the Effectiveness and Contribution of Local Taxes as a Source of Regional Original Income in South Kalimantan Province (2014-2022 Period) - Rezti Rezti (PT. Hanken SUkses Jaya, 2023)
This research was conducted to determine the effectiveness and contribution of local taxes to local revenue in South Kalimantan Province for the period 2014 - 2022. It is a consequence of the regional government in carrying out regional autonomy where the regional government needs funding sources to carry out its main tasks and functions in the region. This study uses quantitative descriptive techniques and documentation. The research data in this paper is secondary data. Based on the results of the analysis, shows that in 2015, 2017, and 2020 the effectiveness of the realization of tax revenues for the Province of South Kalimantan is included in the criteria of being quite effective. While 2014, 2016, 2018, 2019, and 2021 are included in the effective criteria. And the remainder in 2022 is included in the very effective criteria because the realization of South Kalimantan Province's tax revenue reached 106.94%. The results of the contribution analysis show that the highest contribution rate was in 2014, namely 82.65%, and the lowest in 2022, amounting to 41.71%. The advice given by the author in this study is that the South Kalimantan Provincial Revenue Service can improve its performance in collecting data on all potential local taxes, carry out strict supervision in the tax collection process, and educate taxpayers, the South Kalimantan Provincial Revenue Service. Conduct tax intensification and extensification to increase revenue from regional taxes. As well as facilitating procedures in tax collection. Keywords: effectiveness, contribution, PAD, local taxes.